PENGETAHUAN DAN STIGMA MASYARAKAT TENTANG PENYAKIT KUSTA DI DESA AMBESIA BARAT KECAMATAN TOMINI KABUPATEN PARIGI MOUTONG - Niswa Salamung; Ni Ketut Elmiyanti; AA Gede Raka Adi Putra (Sekolah Tinggi Ilmu Kesehatan Indonesia Jaya Palu, 2023)
Leprosy has a broad influence on the lives of sufferers not only in terms of health which can cause permanent disability but also causes problems in marriage, employment, interpersonal relationships, and busi-ness activities. The purpose of this study was to gain knowledge and community stigma about leprosy in Ambe-sia Barat Village, Tomini District, Parigi Moutong Regency. This type of research is descriptive. The variables in this study are knowledge and attitudes. The population in this study were all the people of West Ambesia Village who visited the Tinombo Health Center at the time the research was conducted. The sample is 43 re-spondents with accidental sampling technique. The results of this study showed that of the 43 respondents, 81.4% had less knowledge and 14% had good knowledge. People with less stigma are 65.1% and 34.9% have good stigma. The conclusion is that most of the public's knowledge about leprosy has less knowledge and com-munity stigma about leprosy in Ambesia Barat Village, Tomini District, Parigi Moutong Regency, mostly has less stigma. It is hoped that the community will increase their knowledge about leprosy so as not to create a bad stigma in society about leprosy sufferers so that there is no concern for sufferers